Ultra-high resolution photon-counting coronary CT angiography improves coronary stenosis quantification over a wide range of heart rates – A dynamic phantom study - Zsarnoczay, Emese; Fink, Nicola; Schoepf, U. Joseph; O'Doherty, Jim; Allmendinger, Thomas; Hagenauer, Junia; Wolf, Elias V.; Griffith, Joseph P.; Maurovich-Horvat, Pál; Varga-Szemes, Akos; Emrich, Tilman (European Journal of Radiology, 2023)
Purpose: To investigate the effect of using photon-counting detector (PCD)-CT with ultra-high resolution (UHR) on stenosis quantification accuracy and blooming artifacts from low to high heart rates in a dynamic motion phantom. Method: Two vessel phantoms (diameter: 4 mm) containing solid calcified lesions (25%, 50% stenoses), filled with different concentrations of iodine, inside an anthropomorphic thorax phantom attached to a coronary motion simulator were used. Scanning was performed on a PCD-CT system using an ECG-gated mode at UHR and standard resolution (SR) (0.2, 0.6 mm slice thickness, respectively). Images were reconstructed at 60, 80 and 100 beats per minute (bpm) (UHR: Bv56 kernel, quantum iterative reconstruction (QIR) level 3; SR: 55 keV, Bv40 kernel, QIR3). Percent diameter stenosis (PDS) and blooming artifacts were measured by two readers. Results: PDS measurements derived from UHR were more accurate than SR for both lesions at every heart rate (p ≤ 0.005 for all, e.g. 50% lesion SR vs. UHR: at 60 bpm 57.1% [55.2–59.2] vs. 50.0% [48.5–51.2], at 100 bpm 61.0% [58.6–64.3] vs. 52.4% [51.3–54.3]). Overall mean difference across heart rates and lesions compared to the nominal stenoses was 9.2% (Limit of Agreement (LoA), 2.4%/16.0%) for SR vs. 2.4% (LoA, −2.8%/7.5%) for UHR. Blooming artifacts decreased with UHR compared to SR for both lesions at every heart rate (p < 0.001 for all, e.g. 50% lesion SR vs. UHR: at 60 bpm 63.8% [60.6–69.5] vs. 52.5% [50.0–57.5], at 100 bpm 70.2% [64.8–78.1] vs. 56.1% [51.2–60.8]). Conclusions: This motion phantom study demonstrates improved stenosis quantification accuracy and reduced blooming artifacts with UHR-PCD-CT compared to SR, independent of heart rate.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Cardiac imaging techniques; Computed tomography angiography; Coronary artery disease; Photon counting detector